Comparison the salivary streptococcus mutans levels between caries-active and caries-free children from Birjand, Iran: A case-control study - Ebrahim Shafaie; Zahra Badri; Hamid Salehiniya; Hamid Abbaszadeh (Heliyon, 2024)
Objective: Dental plaque bacteria, including Streptococcus mutans (SM), play a role in the pathogenesis of the dental caries. There are conflicting results regarding the association of salivary SM level and dental caries susceptibility. Our aim was to compare salivary SM levels in colony-forming units (CFU) between children with active caries and caries-free children in Birjand, Iran. Methods: This case-control study included 61 six-year-old children referred to health centers in Birjand city, Iran, in 2022. The children were divided into two groups: case (dmft/DMFT>0 with active caries) (including 31 children) and control (dmft/DMFT = 0 [caries-free]) (including 30 children). Demographic information and dental history were recorded. Oral examinations were also performed by the dentist. Unstimulated saliva samples were collected from children. The number of salivary SM colonies was determined using the microbial culture and confirmed using the polymerase chain reaction (PCR). The data were analyzed using Chi-square and T-tests at a significance level of p < 0.05. Results: The mean number of SM colonies was 126.24 ± 92.78 CFU/ml and 92.38 ± 75.34 CFU/ml in case and control groups, respectively. No significant difference was found in salivary SM levels between case and control groups (P = 0.125). No significant association was observed between caries experience with gender (P = 0.363), type of school (public/private) (P = 0.296), receiving oral health education (P = 0.072) and frequency of tooth brushing (P = 0.935). The mean gingival index (P = 0.001) and plaque index (P = 0.025) in case group were significantly higher than control group. Conclusion: There is no significant difference in salivary SM levels between caries-active and caries-free children in Birjandi children.